Comparative Study Of Piriformospora Indica And Salicylic Acid On The Growth Promotional Activity Of Artemisia Annual - PORI DEKA,; DEBABRAT BAISHYA, (International Journal of Pharma and Bio Sciences, 2015)
Salicylic acid and Piriformospora indica colonized plants were reported as potent enhancers of growth and photosynthetic activity. The present study was conducted to study the comparative alteration of plant growth and photosynthetic activity of the medicinal plant Artemisia annua treated with P. indica and salicylic acid under in vitro condition. The in vitro grown plantlets treated with P. indica showed a higher value in all the growth parameter and photosynthetic pigments content followed by salicylic acid. The callus showed highest values of fresh weight on salicylic acid treatment.